A novel solar-powered active low temperature differential Stirling pump. (September 2015) - Jokar, H.; Tavakolpour-Saleh, A.R.
Abstract: This paper presents a novel solar-powered active Stirling converter with liquid power piston and solid controllable displacer. First, the working principle of the proposed converter is described. Then, finite time thermodynamic approach incorporating heat transfer equations are employed to determine gas temperatures in hot and cold spaces based on the assumption of imperfect regeneration. Accordingly, pressure variation of the gas due to reciprocating motion of the displacer piston is investigated using the obtained gas temperatures and Schmidt theory. Next, total work done by the converter and thermal efficiency are evaluated. Kinematic and dynamic equations governing the pump system are presented and the water flow characteristics in suction and discharge states are investigated. A simulation study is carried out through coupling and simultaneously solving the obtained equations. An optimization scheme is thus conducted to find an optimum frequency of the active converter so that a maximum power is generated. The influences of regenerator efficiency, dead volumes, and water head on the optimum operating frequency and the generated power are investigated. Finally, the proposed converter is constructed and primarily tested. The experimental outcomes clearly reveal the feasibility of pumping water at low temperature difference through the proposed active Stirling pump. Highlights: A novel solar-powered active low temperature differential Stirling pump was presented. A comprehensive mathematical model was proposed for the active converter. An optimization scheme was conducted to find the optimum frequency of the converter. The experimental active Stirling pump was constructed and primarily tested. Experimental results were in a good agreement with a part of the simulation outcomes.